Factors associated with complications in total laryngectomy without microvascular reconstruction. Issue 11 (11th October 2018) - Helman, Samuel N.; Brant, Jason A.; Kadakia, Sameep K.; Newman, Jason G.; Cannady, Steven B.; Chai, Raymond L.
Abstract: Background: There is little population‐level data evaluating risk factors for postoperative complications after total laryngectomy. Methods: We conducted a retrospective review of the American College of Surgeons National Quality Improvement Program identifying patients who underwent total laryngectomy as a primary procedure from 2005 to 2014. Multivariate analysis was performed to identify variables that were independently associated with overall and major complications. Results: Eight hundred seventy‐one cases met inclusion criteria. Three hundred twenty‐eight patients (37.7%) had complications, with operative time (hours; P < .0001), class III ( P < .001) wound status, and patient age (decade; P = .003) associated with overall complications. Two hundred one patients had major complications that were associated with steroid use ( P = .01) and class III ( P = .0083) wound classification. Preoperative hematocrit was correlated with a reduction of all and major complications on multivariate analysis ( P < .0001 and P = .036). Conclusion: Identifying and optimizing risk factors may improve outcomes in total laryngectomy.